Antioxidant Nanoparticles for Concerted Inhibition of α-Synuclein Fibrillization, and Attenuation of Microglial Intracellular Aggregation and Activation - Zhao, Nanxia; Yang, Xue; Calvelli, Hannah R.; Cao, Yue; Francis, Nicola L.; Chmielowski, Rebecca A.; Joseph, Laurie B.; Pang, Zhiping P.; Uhrich, Kathryn E.; Baum, Jean; Moghe, Prabhas V. (Frontiers in Bioengineering and Biotechnology, 2020)
Parkinson’s Disease is characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta, the extracellular accumulation of toxic α-synuclein (αSYN) aggregates, and neuroinflammation. Microglia, resident macrophages of the brain, are one of the critical cell types involved in neuroinflammation. Upon sensing extracellular stimuli or experiencing oxidative stress, microglia become activated, which further exacerbates neuroinflammation. In addition, as the first line of defense in the central nervous system, microglia play a critical role in αSYN clearance and degradation. While the role of microglia in neurodegenerative pathologies is widely recognized, few therapeutic approaches have been designed to target both microglial activation and αSYN aggregation. Here, we designed nanoparticles (NPs) to deliver aggregation-inhibiting antioxidants to ameliorate αSYN aggregation and attenuate activation of a pro-inflammatory microglial phenotype. Ferulic acid diacid with an adipic acid linker (FAA) and tannic acid (TA) were used as shell and core molecules to form NPs via flash nanoprecipitation. These NPs showed a strong inhibitory effect on αSYN fibrillization, significantly diminishing αSYN fibrillization in vitro compared to untreated αSYN using a Thioflavin T assay. Treating microglia with NPs decreased overall αSYN internalization and intracellular αSYN oligomer formation. NP treatment additionally lowered the in vitro secretion of pro-inflammatory cytokines TNF-α and IL-6, and also attenuated nitric oxide and reactive oxygen species production induced by αSYN. NP treatment also significantly decreased Iba-1 expression in αSYN-challenged microglia and suppressed nuclear translocation of nuclear factor kappa B (NF-κB). Overall, this work lays the foundation for an antioxidant-based nanotherapeutic candidate to target pathological protein aggregation and neuroinflammation in neurodegenerative diseases.